Investigation of mechanical properties and form error of the components fabricated by rapid prototyping: A review. (2021) - Maurya, Nagendra K.; Maurya, Manish; Saxena, Ambuj; Tyagi, Avdesh; Kiran, Gopal; Singh, Himanshu; Tripathi, Happy; Kumar, Prince; Yadav, Sachin
Abstract: 3D printing is emerging as one of the most important and advanced technique of manufacturing. Nowadays, manufacturing industries is focusing on reduction of lead time of product development and cost of product. 3D printing has large application in many fields such as aerospace and defence, medical, consumer goods etc .The purpose of this study was to present a concise review on rapid manufacturing processes. This paper includes historical development, available technologies, materials and their tangible benefits. Researchers have analyzes the influence of process parameters like orientation, layer thickness, air gap, printing direction etc. on properties of components which are fabricated through 3D printing. The noble contribution of this paper is to present systematic approach to enable potential for academics user as well as industry persons to select appropriate technology.